Arrestee Drug Abuse Monitoring (ADAM) Program in the United States, 2003 ([Verlag nicht ermittelbar], 2004)
The goal of the Arrestee Drug Abuse Monitoring (ADAM) Program is to determine the extent and correlates of illicit drug use in the population of booked arrestees in local areas. Data were collected in 2003 up to four separate times (quarterly) during the year in 39 metropolitan areas in the United States. The ADAM program adopted a new instrument in 2000 in adult booking facilities for male (Part 1) and female (Part 2) arrestees. The ADAM program in 2003 also continued the use of probability-based sampling for male arrestees in adult facilities, which was initiated in 2000. Therefore, the male adult sample includes weights, generated through post-sampling stratification of the data. For the adult male and female files, variables fell into one of eight categories: (1) demographic data on each arrestee, (2) ADAM facesheet (records-based) data, (3) data on disposition of the case, including accession to a verbal consent script, (4) calendar of admissions to substance abuse and mental health treatment programs, (5) data on alcohol and drug use, abuse, and dependence, (6) drug acquisition data covering the five most commonly used illicit drugs, (7) urine test results, and (8) for males, weights.